Charlie Pippin - Boyd, Candy Dawson (New York : Puffin Books, 1988)
Spunky eleven-year-old Charlie hopes to understand her rigid father by finding out everything she can about the Vietnam War, the war that let him survive but killed his dreams.
Keywords: Fathers and daughters -- Fiction; Vietnam War, 1961-1975 -- Fiction; African Americans -- Fiction